DAMPAK PORNOGRAFI TERHADAP PERKEMBANGAN PERILAKU REMAJA - Siti Fatimah (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Adolescence is a period of transition from childhood to adulthood with an age range of 12-22 years, during which a maturation process occurs, both physical and psychological. According to WHO, anemia is the biggest nutritional problem in adolescents which can have a negative impact on their performance and cognitive growth. Increased knowledge through a health education approach is an activity to provide and improve cognitive, affective to individuals in this case young women in order to maintain and strengthen their own health. Health education about anemia in young women can provide knowledge about nutrition in adolescents in order to prevent anemia in young women. Exposure to pornography in children is mainly obtained through the internet which is exacerbated by "lifestyle" and lack of supervision, no communication, demands are too high, violence against children. children, not knowing the potential of children, as well as discrimination from parents and the environment can trigger teenagers to be exposed to pornography. The sophistication of technology makes it easy to access sex-laden content, namely pornography, so that many teenagers enjoy this and become addicted. The method in implementing community service is carried out by lecture, discussion and question and answer methods using a flipchart while the output obtained is increased awareness and knowledge of adolescents about the impact of pornography on the development of adolescent behavior in SMA N 1 Tegal. The outputs obtained are education and understanding to children about the dangers of pornography and teenagers so that there are no deviations and bad behavior in the process of developing adolescent behavior at SMA N 1 Tegal.